Thailand’s Low-Growth Economy: An Analysis of Structural Factors and Challenges in the ASEAN Context - Dumrongkul, Warachai (Thai Social Science Journal, 2026)
This article examines the issue of low economic growth in Thailand over the past decade, focusing on the structural factors that constrain the country’s long-term growth potential. The study aims to analyze the key determinants of Thailand’s economic slowdown and to compare the country’s economic performance with other Southeast Asian economies. The findings indicate that Thailand is experiencing a period of low economic growth driven by several structural constraints. Major factors include the slowdown in export performance, which has historically been a key engine of the Thai economy, increasing economic competition from neighboring countries such as Vietnam and Indonesia, and persistently high levels of household debt that constrain domestic consumption. In addition, Thailand’s economic structure continues to rely heavily on medium-value manufacturing activities and has yet to fully transition toward an innovation-driven and technology-based economy. These structural limitations suggest that Thailand faces the risk of remaining trapped in the middle-income trap if structural reforms are not effectively implemented. The study also finds that the low-growth environment has broader implications for Thailand’s economic system, including a slowdown in private investment, declining national competitiveness, and potential risks to long-term economic growth. Without appropriate policy responses, these challenges may weaken Thailand’s ability to compete within the regional economy. Therefore, the article proposes that addressing Thailand’s low economic growth requires comprehensive structural reforms, particularly upgrading the economic structure toward high-value industries, promoting the digital economy and innovation, reforming industrial policies, and improving workforce skills to meet the demands of a modern economy. These measures are essential for strengthening Thailand’s competitiveness and ensuring sustainable economic growth in the long term.